Tratamiento contable de una concesión camaronera según NIC38. - Arteaga Murillo, Cristhel Aylin (Universidad Técnica de Machala, 2022)
The research presents that of intangible assets according to International Accounting Standard 38 and demonstrates a correct accounting that is complex and challenges professionals, researchers and students at the time of its interpretation and application, therefore, this work aims to analyze intangible assets under the guidance of international accounting standard 38 for correct recognition and measurement in the company; A descriptive study is developed using deductive methods to achieve the objectives, this is stated that more specific statements are derived from general premises, which allows to have a clearer perspective of the subject that is being developed and to know different cases in the business field; As a result of the investigation, the accounting treatment of the government subsidy, its acquisition, the amortization of each year associated with the provision of the service is carried out, and for the closing, capitalizations of the accounting accounts are shown where the adequate accounting is reflected, prior analysis of recognition as such of the intangible asset, reflecting the very approach of intangible assets, it is concluded that they are very important for companies, since they generate greater performance and production in the course of the activities carried out, in addition to the analysis carried out to IAS 38, the necessary knowledge was obtained to apply the correct accounting treatment of intangible assets at a given time.
La investigación presenta el estudio de los activos intangibles según la Norma Internacional de Contabilidad 38 y demuestra una correcta contabilización que es compleja y desafía a los profesionales, investigadores y estudiantes al momento de su interpretación y aplicación, por tanto, este trabajo tiene como objetivo, analizar los activos intangibles bajo la guía de la norma internacional de contabilidad 38 para un correcto reconocimiento y medición en la empresa; se desarrolla un estudio descriptivo utilizando métodos deductivos para lograr los objetivos planteados, esto se debe a que de premisas generales se derivan enunciados más específicos, lo que permite tener una perspectiva más clara del tema que se está desarrollando y conocer distintos casos en el ámbito empresarial; como resultado de la investigación, se realiza el tratamiento contable de la subvención de gobierno, su adquisición, la amortización de cada año asociados a la prestación del servicio, y para el cierre se muestran mayorizaciones de las cuentas contables donde se refleja la contabilización adecuada, previo análisis de reconocimiento como tal del activo intangible, reflejando el propio enfoque de los activos intangibles, se concluye que son muy importantes para las empresas, puesto que generan mayor rendimiento y producción en el transcurso de las actividades que realiza, además, del análisis realizado a la NIC 38 se obtuvo conocimiento necesario para aplicar en correcto tratamiento contable de los activos intangibles en un momento determinado.
Keywords: ACTIVOS INTANGIBLES; AMORTIZACIÓN; SUBVENCIÓN; PASIVO DIFERIDO